Pengaruh Inventory Turnover terhadap Perubahan Laba Bersih PT Sampoerna Periode 2016–2024 - Yuliana Oktavianus; Alexander Sandhika Putera Laudhisa; Elizabeth Tiur Manurung (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to analyze the effect of inventory turnover on changes in net profit at PT Hanjaya Mandala Sampoerna Tbk during the period 2016–2024. PT Hanjaya Mandala Sampoerna Tbk is one of the major companies involved in the cigarette industry in Indonesia, which faces significant challenges in managing inventory and maximizing profitability. This study uses a quantitative approach with a simple linear regression analysis method to examine the relationship between inventory turnover and changes in the company's net profit. The data used in this study are secondary data obtained from the company's quarterly financial reports, which are accessed through the official website of the Indonesia Stock Exchange. The analysis results show that inventory turnover has a significant influence on changes in the company's net profit. The adjusted R square value of 21.65 percent indicates that inventory turnover can explain part of the variability in changes in net profit. This means that efficient inventory turnover can be an important factor in determining a company's profitability. In addition, the F significance value of 0.0042 indicates that the regression model used is statistically significant, which means the relationship between inventory turnover and net profit does not occur by chance. The positive relationship between the variables indicates that the higher the efficiency of inventory turnover, the company's net profit tends to increase. These findings underscore the importance of effective inventory management in improving company profitability, particularly amidst the ever-changing challenges of the cigarette industry. Therefore, inventory turnover can be used as a managerial indicator to assess a company's operational effectiveness and as a reference for strategic decision-making to maintain long-term profit stability and enhance market competitiveness.